IMPLEMENTATION OF PROPHETIC LEADERSHIP FROM THE PERSPECTIVE OF THE QUR'AN AND HADITH IN ISLAMIC EDUCATIONAL INSTITUTIONS - Evi Nur Halimah (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2024)
Leadership is a daily issue in family life, society, organization,state and nation. Leadership affects the family order, the progress of the organization and even thestate and nation. More broadly, the leadership tasks given by God to humans are diverse. Starting from the leadership position, himself, a family, an organization, even a large organization like a nation. In addition to the diverse leadership tasks, leadership models are also diverse. This is partly due to the different characteristics of each person. However, Islam does not simply surrender to the leadership model based on character. Islam has provided direction and examples to become a good leader. These examples have been clearly conveyed in the Qur'an and Hadith. In this article, the author discusses specifically the leadership models of Manifesto Leadership and Situational Leadership which are reviewed from the perspective of the Qur'an and Hadith, as well as their implementation in Islamic educational institutions.